Performance and feasibility of reactive surveillance and response strategies for malaria elimination in Vietnam: a mixed-methods study - Win Han Oo; Xuan Thang Nguyen; Thi Van Anh Ngo; Duc Thang Ngo; Win Htike; Nilar Aye Tun; Kaung Myat Thu; Julia Cutts; T Hong Phuc Nguyen; May Chan Oo; Ei Phyu Htwe; Aung Khine Zaw; et al. (Malaria Journal, 2023)
Abstract Background To enhance malaria elimination, Vietnam adopted a Reactive Surveillance and Response (RASR) Strategy in which malaria case notification and investigation must be completed within 2 days followed by a focus investigation within 7 days. The nationwide performance of Vietnam’s RASR strategy has yet to be evaluated. This study aims to evaluate the performance and feasibility of RASR in Vietnam, thereby providing recommendations for improved RASR. Methods To assess malaria RASR in Vietnam, a mixed-methods study of (1) secondary data analysis of nationwide malaria case-based dataset from 2017 to 2021; (2) a quantitative survey, and (3) qualitative in-depth interviews and focus group discussions administered to central, provincial and district level stakeholders/staff and to the commune and community level front line health services providers was conducted. Results In Vietnam, there are guidelines and procedures for implementation of each step of RASR. The completeness of case notification on the reported monthly aggregated data was very high in both the paper-based (12,463/12,498, 99.7% in 2017–2020) and electronic reporting systems (467/467, 100% in 2021 when electronic reporting was introduced); however, there were delays in notification while using the paper-based system (timely notification—7,978/12,498, 63.8%). In 2021, the completeness (453/467, 97.0%) and timeliness (371/467, 79.4%) of case investigation were found to be high. Reactive case detection was the major focus investigation response, with fever screening achievement of 88.6% (11,481 / 12,965) and 88.5% (11,471 / 12,965) among index case and neighbouring household members, respectively. Conclusions Overall, there was policy commitment for implementation of RASR in Vietnam. The completeness and timeliness of case notification and case investigation were high and improved after the introduction of the electronic reporting system. More evidence is required for reactive case detection in defining the screening area or population.